PENGARUH EKSTRAK RUMPUT LAUT (EUCHEMA SP.) TERHADAP HISTOLOGI SEL Β PANKREAS PADA RATTUS NOVERGICUS GALUR WISTAR DENGAN DIABETES MELLITUS YANG DI INJEKSI ALOKSAN - Sari, Kurniati Maya (Ensiklopedia Sosial Review, 2020)
Metabolic diseases such as diabetes mellitus tends to increase, diabetes is not well controlled can cause oxidative stress. Oksidatf stress can increase ROS and antioxidants in our bodies may decrease, resulting in cell damage one pancreatic β cells. To overcome the effects of free radicals on penderit DM and the possibility of complications that need an exogenous antioxidants include seaweed. The purpose of this study was to determine the effect of seaweed extract (Euchema SP.) Against pancreatic β cell histology in wistar rats with alloxan-induced hyperglycemia. This research type experimental dalah Post Test Only Control Group Design conducted on 25 male rats aged 2-3 months ISTAR. Rats were divided into five kelompokyaitu 1 negative control group (KN) were given a standard diet, the first group of positive control (KP) induced alloxan in Intra Peritoneal 150 mg / kg, 3 Kelompom induced alloxan and given a seaweed extract (PI): 174mg / 200gr BB rats (P2): 352, 8 mg / 200 g BB rat, (P3): 529.2 mg / 200 g BB rats. The treatment was done for 48 days. Data were statistically processed using ANOVA test formula with a 95% confidence level. Results showed The average number of pancreatic β cells in the negative control (45.8 ± 8.871), the group of the positive controls (110 ± 1581) on the treatment kelompk occurred increasing the number of pancreatic beta cells, PI (176.6 ± 2.074), P2 (17.25 ± 2.02) P3 (30.6 ± 40.99). Annova test showed significant difference with P Value 0.0005 Alpha P ≤ 0.05. It is concluded that the extract of seaweed (Euchema SP.) On histological cell β pancreas in rats Wistar hyperglycemia induced by alloxan, the results of this study can be applied in humans, especially people with diabetes because it has been tested, it extracts umput sea can repair cells pancreatic β on the state of hyperglycemia.